2018
DOI: 10.1002/1878-0261.12169
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of VEGF‐dependent angiogenesis and tumor angiogenesis by an optimized antibody targeting CLEC14a

Abstract: The C‐type lectin‐like domain of CLEC14a (CLEC14a‐C‐type lectin‐like domain [CTLD]) is a key domain that mediates endothelial cell–cell contacts in angiogenesis. However, the role of CLEC14a‐CTLD in pathological angiogenesis has not yet been clearly elucidated. In this study, through complementarity‐determining region grafting, consecutive deglycosylation, and functional isolation, we generated a novel anti‐angiogenic human monoclonal antibody that specifically targets CLEC14a‐CTLD and that shows improved stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…tested a human colorectal cancer cell line HCT116 as well as a bevacizumab‐resistant version of this line. Both cell lines showed significant reductions in in vivo angiogenesis following treatment with CLEC14A antibodies when these cells were embedded in Matrigel and injected subcutaneously . This suggests a possible use for targeting of CLEC14A in patients that have acquired resistance to VEGF blockade.…”
Section: Considerations and Perspectivesmentioning
confidence: 87%
See 1 more Smart Citation
“…tested a human colorectal cancer cell line HCT116 as well as a bevacizumab‐resistant version of this line. Both cell lines showed significant reductions in in vivo angiogenesis following treatment with CLEC14A antibodies when these cells were embedded in Matrigel and injected subcutaneously . This suggests a possible use for targeting of CLEC14A in patients that have acquired resistance to VEGF blockade.…”
Section: Considerations and Perspectivesmentioning
confidence: 87%
“…Finally, these antibodies could reduce HUVEC cell migration and tube formation based on in vitro assays. Further studies optimised the solubility and stability of the CLEC14A CTLD‐targeting antibodies and showed that they could block angiogenesis in mouse models utilising Matrigel plugs injected with recombinant VEGF or human tumour cells . Collectively, these results suggest that the CTLD of CLEC14A has functional roles in angiogenesis.…”
Section: Clec14a Roles In Vascular Biology and Cancermentioning
confidence: 96%
“…The C-type lectin domain has been shown to engage other matrix proteins, such as multimerin 2 (MMRN2) and heat-shock protein 70-1A (61,62). Antibodies blocking these interactions or targeting the C-type lectin domain have been shown to decrease cell migration and tumor angiogenesis in a manner dependent on MMRN2 (42,62) or VEGFA (68). Whether these antibodies block the GAG-binding site is not known.…”
Section: Lphams and The Heparan Sulfate Interactomementioning
confidence: 99%
“…CLEC14A has also been reported to regulate pro-angiogenic phenotypes such as filopodia formation, cell migration and tube formation in HUVECs (31,32); it localizes to the inter-cellular boundary and regulates cell adhesion through its CTLD (31). Targeted neutralization of CLEC14A using an anti-CTLD antibody was shown to inhibit endothelial cell migration, cell-cell contact and tube formation by blocking CTLD-CTLD interactions, and downregulating CLEC14A expression at the endothelial cell surface (36,37). A Stable Isotope Labelling with Amino Acids in Cell Culture-based proteomics study showed the upregulation of CLEC14A expression during tubule morphogenesis, and the analysis of post-translational modifications of CLEC14A identified a phosphorylation site at Ser483, near the PDZ-binding domain in the cytoplasmic tail (38).…”
Section: Clec14amentioning
confidence: 99%